2013
DOI: 10.1186/1471-2431-13-49
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessment of the gastroesophageal microbiome in VLBW neonates

Abstract: BackgroundThe distal GI microbiota of hospitalized preterm neonates has been established to be unique from that of healthy full-term infants; the proximal GI, more specifically gastroesophageal colonization has not been systematically addressed. We prospectively evaluated early colonization of gastroesophageal portion of the GI tract of VLBW infants.MethodsThis study involved 12 infants admitted to a level III NICU with gestational age (GA) 27 +/− 0.5 weeks and birth weight 1105 +/− 77 grams. The gastroesophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
3

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
6
19
0
3
Order By: Relevance
“…Additionally, our own lab has found that the placenta harbors a unique microbiome, and that this microbiome differs in term and preterm subjects (Figure 1) (Aagaard et al, 2014). Supporting our observations, a bacterium found in the amniotic fluid of preterm patients was most likely to be found in the oral cavity as well, rather than the vaginal cavity (Bearfield, 2002; Douvier et al, 1999; Han et al, 2006) and both term and preterm neonates appear to be colonized early with bacteria normally found in the oral cavity (Figure 1) (Human Microbiome Project Consortium, 2012; Jost et al, 2012; Milisavljevic et al, 2013; Palmer et al, 2007). When Fusobacterium nucleatum is isolated from preterm patients and injected intravenously into pregnant mice, the placenta becomes selectively colonized with bacteria while other organs, such as the liver or spleen, do not (Han et al, 2004).…”
Section: The Microbiome Parturition and Preterm Birthsupporting
confidence: 83%
“…Additionally, our own lab has found that the placenta harbors a unique microbiome, and that this microbiome differs in term and preterm subjects (Figure 1) (Aagaard et al, 2014). Supporting our observations, a bacterium found in the amniotic fluid of preterm patients was most likely to be found in the oral cavity as well, rather than the vaginal cavity (Bearfield, 2002; Douvier et al, 1999; Han et al, 2006) and both term and preterm neonates appear to be colonized early with bacteria normally found in the oral cavity (Figure 1) (Human Microbiome Project Consortium, 2012; Jost et al, 2012; Milisavljevic et al, 2013; Palmer et al, 2007). When Fusobacterium nucleatum is isolated from preterm patients and injected intravenously into pregnant mice, the placenta becomes selectively colonized with bacteria while other organs, such as the liver or spleen, do not (Han et al, 2004).…”
Section: The Microbiome Parturition and Preterm Birthsupporting
confidence: 83%
“…The total number of bacteria decreased over the first 4 wk in one study where Bacteroides and Escherichia coli were predominant (14). On the contrary, in another study, the total number of bacteria increased and Staphylococcus epidermidis was the main colonizer (15). Duodenal aspirates from preterm infants contained none or few Gram-positive bacteria in the first days of life with increasing probability of colonization with Staphylococci, Enterococci, and Gram-negative bacteria, especially Escherichia coli, and Klebsiella pneumoniae and K. oxytoca, over the first weeks.…”
Section: Discussionmentioning
confidence: 91%
“…Only few groups have investigated the early colonization of the upper part of the gastrointestinal tract in preterms, but they found that the microbiomes of gastric aspirates are unstable and consisting of low bacterial counts (14)(15)(16). The total number of bacteria decreased over the first 4 wk in one study where Bacteroides and Escherichia coli were predominant (14).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the authors found that healthy, term neonates that were breast fed had increased diversity in their intestinal microbiome when compared with hospitalized, preterm infants using PCR-DGGE analysis (Schwiertz et al 2003). Additional studies have confirmed that the microbiome of infants with conditions like PTB, very low birth weight infants, or necrotizing enterocolitis, also have an altered microbiome (Schwiertz et al 2003; Hällström et al 2004; Milisavljevic et al 2013; Wang et al 2013). However, it is unclear if these alterations are caused by early gestational age at delivery or hospitalization because neonatal exposure in early life is pertinent to the establishment of the microbiome.…”
Section: Beyond the Vaginal Microbiome: Early Infant Colonizationmentioning
confidence: 93%